A hierarchical multiscale model for the elastic-plastic damage behavior of 3D braided composites at high temperature. (18th August 2020) - He, Chunwang; Ge, Jingran; Zhang, Binbin; Gao, Jiaying; Zhong, Suyang; Liu, Wing Kam; Fang, Daining
Abstract: A hierarchical multiscale model is established to reveal the failure mechanism of three-dimensional (3D) braided composites at high temperature. Firstly, the tensile and bending tests of the composites were performed at three different temperatures, and the properties of microscale constituents, i.e., carbon fiber, epoxy resin and interface, were also calibrated by experiments at different temperatures. Then, the elastic-plastic damage constitutive laws were proposed to characterize the mechanical behavior of microscale and mesoscale components. These constitutive models were implemented by a user-defined subroutine UMAT in ABAQUS. Finally, based on the homogenization procedure and the multiscale analysis method, the effects of temperature on microscale, mesoscale and macroscale properties of 3D braided composites were analyzed sequentially. The results showed that the temperature has the significant effects on the performances of 3D braided composites. With the increase of temperature, the properties of 3D braided composites decreased, and the failure modes changed from fiber breakage to matrix plastic deformation. Besides, the macroscopic simulation of strain fields agreed well with the DIC measurements and the temperature-dependent failure modes agreed well with SEM observation. It is expected that the established multiscale framework can predict high-temperature behavior of 3D braided composites and reveal the different failure mechanisms at different temperatures. Graphical abstract: Image 1 Highlights: The effect of temperature on the failure mechanism of 3D braided composites is revealed by experiments and simulation. A hierarchical multiscale framework of the temperature-dependent elastic-plastic damage behavior is developed. A full-scale FEM model is established to simulate the macroscale strain fields and compare with the DIC measurement.